PENGAWASAN PROGRAM PENGEMBANGAN KARET RAKYAT DI DESA NGARAK - Suanda E.21109007 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is that the program of rubber seeds from many incoming government , but there are still many people who have not been able to take advantage of the program , as evidence of this phenomenon is that the rubber has been planted yet can produce optimal rubber . The purpose of this study is to want to examine and describe the supervision of rubber seedlings to farmers in the village of District Overseer Ngarak by Plantation Office of West Kalimantan Province . The results showed that the Plantation Office of West Kalimantan province has tried to carry out strict control over seed aid to farmers in the village of Ngarak District Overseer for the right target and avoid deviations .However , monitoring is done can not be optimized because the officers were a little constrained by the number , the less the quality of human resources , lack of funds and accommodation vehicle and a remote location and poor road access . In addition , there has been no coordination between field officers with the District Head for aid awarded directly without going through the district . In addition , there is no proper coordination with farmers , making it difficult to identify farmers who divert the aid to farmers in developing rubber seedlings failed because of technical problems such as the high cost of constrained fertilizers and medicines . Responding to phenomena Plantation Office of West Kalimantan Province is expected to improve oversight of rubber seedlings to farmers in the village of Ngarak District Overseer , for example by mesiasati shortage of financial resources and inadequate facilities to submit a request to the authorities . In addition , the Agriculture Agency of West Kalimantan can also improve coordination with intensive coordination with village officers who can be trusted . In addition , field officer assigned to the Plantation Office of West Kalimantan Province is also expected to work optimally , so many irregularities that may occur in the field can be immediately identified and found a way out . Keywords : Monitoring , Distribution , Seeds , Rubber